Factors Affecting Students’ Difficulties in Speaking Performance of The Tenth Grade Students of SMA Negeri 1 Tiworo Kepulauan - Hendriati Afebri; Aderlaepe .; Khusnun Muhsin (Journal of English Education and Teaching, 2019)
Students’ speaking performance could be affected by factors that come from performance conditions (time pressure, planning, standard of performance and amount of support), affective factors (such as motivation, confidence and anxiety), listening ability, topical knowledge and feedback during speaking activities. The purpose of this study was to analyze, describe and determine factors affecting students’ difficulties in speaking performance of the tenth-grade students of SMA Negeri 1 Tiworo Kepulauan. This study employed quantitative design in the form of survey. The samples were 30 students of X MIA 2 which were taken by using random sampling. The data were collected by using close ended questionnaire and were analyzed by using SPSS version 16. The results of this research showed that of the three factors affecting students’ difficulties in speaking, the highest percentage was linguistic factors including grammar, vocabulary and pronunciation. It was concluded that the students got difficulties in performing speaking task. Keywords: Speaking Performance, Students’ Difficulties